Factors associated with the utilization of community assessment models among Japanese nurses. Issue 2 (12th September 2021) - Shiomi, Misa; Yoshioka‐Maeda, Kyoko; Kotera, Sayaka; Ushio, Yuko; Takemura, Kazuko
Abstract: Objectives: This study aimed to identify factors related to the practical utilization of community health needs assessment (CHNA) models that public health nurses (PHNs) learned in their fundamental education. Design: A nationwide questionnaire survey was conducted via postal mail. Sample: We randomly selected 630 public health institutes in Japan. The participants were 3397 full‐time novice and mid‐level PHNs. Measurements: The questionnaire included the participants' basic personal information, six items regarding the perception of CHNA with a 4‐point Likert scale, learned models in their undergraduate education, their utilization in practical settings, and the reasons for their answer in narrative form. Results: There were 951 valid responses. The results of logistic regression showed that the significant positively factors with model utilization were perception of CHNA as "not troublesome" or "not impossible as they learned, " continuing education with 5 years of experience, and identification of the learned model in continuing education. Furthermore, the results of text mining showed the reasons for non‐utilization of the model included being "busy" and having a lack of "opportunity." Conclusions: This study showed the associated factors with rare utilization of a learned model for PHNs. These findings may suggest improvement of continuing education and development of an appropriate assessment model.